Changes in Seismicity Pattern Due to the 2016 Kumamoto Earthquakes Identify a Highly Stressed Area on the Hinagu Fault Zone - K.Z. Nanjo; J. Izutsu; Y. Orihara; M. Kamogawa; T. Nagao (Geophysical Research Letters)
Abstract A highly stressed area where eventual ruptures have often been observed to nucleate is characterized by low b values of earthquake frequency‐size distribution. Crustal deformation due to the occurrence of large earthquakes causes stress perturbation in nearby regions, so an investigation into spatiotemporal b values can play a crucial role in the distribution of postseismic hazards after the 2016 Kumamoto earthquake sequence along the Futagawa‐Hinagu fault zone, which culminated in the magnitude 7.3 mainshock. Together with an analysis of aftershock decay p value that can be used to infer stressing history, a highly stressed area with a characteristic dimension of 10 km at the southern end of the causative faults was found. Our observation is explained by postseismic deformation due to an afterslip on the causative faults and viscoelastic relaxation model. Similar to the Kumamoto mainshock rupture, which started at a low‐b‐value area, the observed highly stressed area shows a high likelihood of future earthquake ruptures.